Transformation of retail banking under the influence of Fintech (Economics and region, 2023)
Given the significant growth in technology and innovation in recent years, retail banking has undergone significant changes. The article discusses the key trends that affect the development of retail banking in the near future. Such trends include the expansion of the use of big data and artificial intelligence to personalize the customer experience. Banks must use data to better understand their customers and offer them more personalized products and services. The development of super-apps, which combine various financial services in one place, was considered. Customers increasingly expect to be able to access all their financial needs in one place. The automation of end-to-end processes to increase the efficiency and productivity of banking activities has been studied. Banks can use automation to simplify and speed up routine processes such as document verification, loan approval and fraud detection. This will allow them to free up time for more creative and strategic tasks. And the use of blockchain technology to increase the security and efficiency of transactions is also substantiated. Blockchain is a decentralized technology that provides increased security and transparency of transactions. It is justified that the considered trends force banks to change and adapt to new conditions in order to remain competitive.
Keywords: retail banking; FinTech; digital banking; personalized customer experience; superapp; blockchain